Electrical Reconnection Program Design for Argentina Roca Line EMUs - XU Qiang; CHEN Mingfeng; SU Zhaolong (机车电传动)
Aiming at the requirement of small marshalling reconnection for flexible passenger flow of Argentina Roca line EMUs, the control program of small marshalling reconnection operation was studied, and train level hard-line and network communication reconnections were discussed. The verification was carried out for two four-marshalling vehicles reconnection.